Examination of the Effects of Conduction Slowing on the Upstroke of Optically Recorded Action Potentials - O’Shea, Christopher; Pavlovic, Davor; Rajpoot, Kashif; Winter, James (Frontiers in Physiology, 2019)
Introduction The upstroke of optical action potentials (APs) recorded from intact hearts are generally recognised to be slower than those recorded with microelectrodes. This is thought to reflect spatial signal averaging within the volume of tissue that makes up the optical signal. However, to date, there has been no direct experimental study on the relationship between CV and optical AP upstroke morphology in the intact heart. Notably, it is known that sodium channel block and gap junction inhibition, which both slow CV, exert differential effects on the upstroke velocity of microelectrode-recorded APs. Whether such differences are evident in optical APs is not known. The present study sought to determine the relationship between tissue CV and optical AP upstroke velocity in intact mouse hearts. Materials and methods Isolated, perfused mouse hearts were stained with the potentiometric dye Rh-237. Fluorescent signals were recorded from across the anterior surface of the left and right ventricles during constant pacing. Maximum rate of change in fluorescence (dF/dtmax) and tissue CV were assessed in control conditions, during an acute period of low-flow ischaemia, and following perfusion of flecainide (1-3mol/L), a sodium channel blocker, or carbenoxolone (10-50mol/L), a gap junction inhibitor. Results During epicardial pacing, an anisotropic pattern was observed in both activation and dF/dtmax maps, with more rapid optical AP upstroke velocities orientated along the fastest conduction paths (and vice versa). Low-flow ischaemia resulted in a time-dependent slowing of ventricular CV, which was accompanied by a concomitant reduction in optical AP upstroke velocity. All values returned to baseline on tissue reperfusion. Both flecainide and carbenoxolone were associated with a concentration-dependent reduction in CV and decrease in optical AP upstroke velocity, despite distinct mechanisms of action. Similar responses to carbenoxolone were observed for low- (156m pixel with) and high- (20m pixel width) magnification recordings. Comparison of data from all interventions revealed a linear relationship between CV and upstroke dF/dt. Conclusion In intact mouse hearts, slowing of optical AP upstroke velocity is directly proportional to the change in CV associated with low-flow ischaemia, sodium channel block and gap junction inhibition.